THE UTILIZATION OF EDUCATIONAL TECHNOLOGY BASED ON ZOOM MEETING AND GOOGLE CLASSROOM IN THE PANDEMIC ERA - Wasehudin Wasehudin; Irfan Anshori (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2021)
This research aims at how Zoom Meeting and Google Classroom media are used as technology media that could be a learning solution in this Covid-19 era. The method used in this study was based on qualitative research based on case studies, where the authors analyzed the collected data to be used as primary data sources in further research. The problem faced by institutions during the pandemic was that there were still most students who did not have adequate communication tools and internet network access. The ineffectiveness of using Zoom Meeting and Google Classroom learning media at the One Roof Middle School in Lontar was caused by the economic level of the parents of students, most of whom rely financially on seafood, so that most of the students found it difficult to provide supporting infrastructure for online learning. In addition, there were still many students who were clueless in the field of information technology (IT), making it difficult for them to operate the two online learning platforms.